Thermally tunable add-drop filter based on valley photonic crystals for optical communications - Sun Lu; Li Xingfeng; Hu Pan; Wang Hongwei; Zhang Yong; Tang Guojing; He Xintao; Dong Jianwen; Su Yikai (Nanophotonics)
Valley photonic crystals (VPCs) provide an intriguing approach to suppress backscattering losses and enable robust transport of light against sharp bends, which could be utilized to realize low-loss and small-footprint devices for on-chip optical communications. However, there are few studies on how to achieve power-efficient tunable devices based on VPCs, which are essential for implementing basic functions such as optical switching and routing. Here, we propose and experimentally demonstrate a thermally tunable add-drop filter (ADF) based on VPCs operating at telecommunication wavelengths. By leveraging the topological protection of the edge state and the distinct property of negligible scattering at sharp bends, a small footprint of 17.4 × 28.2 μm2 and a low insertion loss of 2.7 dB can be achieved for the proposed device. A diamond-shaped microloop resonator is designed to confine the light and enhance its interaction with the thermal field generated by the microheater, leading to a relatively low power of 23.97 mW needed for switching the output signal from one port to the other. Based on the thermally tunable ADF under the protection of band topology, robust data transmission is implemented with an ultrahigh data rate of 132 Gb/s. Our work shows great potential for developing high-performance topological photonic devices with the thermally tunable silicon-based VPCs, which offers unprecedented opportunities for realizing topologically protected and reconfigurable high-speed datalinks on a chip.